A comparison of institutional quality in the South Caucasus: Focus on Azerbaijan - Ibrahim Niftiyev (Proceedings of the European Union's Contention in the Reshaping Global Economy, 2022)
Much has happened in the three countries of the South Caucasus-namely, Azerbaijan, Georgia, and Armenia-since the collapse of the Soviet Union. Political events, institutional reforms, and economic development have resulted in greater economic welfare in these countries after the painful transition period of the 1990s. However, it remains to be seen whether they have achieved any solid results or whether they still have much to accomplish. While the answer is ambiguous, each country has followed a different political, geopolitical, economic, and institutional path and achieved different economic outcomes despite their close geographical proximity to each other. This paper compares the available data on economic and institutional quality in Azerbaijan, Georgia, and Armenia to portray the overall situation in terms of changes in institutional patterns. Then, special attention is given to Azerbaijan, as the country is considered to be oil-rich and thus resource-dependent. A comparative perspective on institutional quality suggests that Georgia has been a leading country in terms of institutions and effective bureaucracy-building, despite having lower economic indicators compared to Azerbaijan. Moreover, while Armenia is positioned between Georgia and Azerbaijan in terms of institutional quality, its economic growth is similar to Georgia's. Lastly, institutional variables (e.g., control of corruption, rule of law, and government effectiveness, and human rights) in Azerbaijan are negatively correlated with oil-related variables. This result aligns with the natural resource curse and Dutch disease theories, which posit that oil boom periods in mineral-rich countries are associated with a deterioration in institutional quality, thereby leading to slower growth. Also, the results are important to build up analytical frameworks to address the Dutch disease or resource curse studies in the case of Azerbaijan in a comparative manner with oil-poor countries even if the scope is limited to the South Caucasian former Soviet Union countries.
Keywords: 330; South Caucasus; Azerbaijan economy; oil boom; institutional quality; correlation analysis